Strategi Pemasaran Potokita di TikTok untuk Meningkatkan Kesadaran Merek - Firmansyah, Ananda Rizqi; Zuhri, Saifuddin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study explores the social media marketing strategy of Potokita Self Studio through the TikTok platform in building brand engagement. The research problem focuses on how content strategies influence audience interaction and loyalty. Using a qualitative descriptive method, data were collected through in-depth interviews with internal stakeholders (owner, content creator, content planner, social media admin) and external users (followers), along with direct observation of the @potokitaselfstudio account. The findings show that Potokita applies a four-pillar strategy based on the Circular Model of SOME (Share, Optimize, Manage, Engage). These strategies include storytelling content creation, insight-based scheduling, structured account management, and interactive engagement such as challenges and giveaways. The study concludes that Potokita’s approach successfully builds emotional connections and enhances audience participation, offering an effective model for digital marketing in small creative businesses.